2011
DOI: 10.5005/jp-journals-10005-1098
|View full text |Cite
|
Sign up to set email alerts
|

Type III Dens Invaginatus with an Associated Cyst: A Case Report and Literature Review

Abstract: Dens invaginatus (dens in dente) is a rare malformation with a widely varied morphology. An unusual presentation of a type III dens invaginatus affecting a conical shaped permanent lateral incisor in an 8-year-old female patient is reported. The presence of a pulp stone and a periapical radiolucency further added onto the complexity of the case. The etiology, pathophysiology, association with other dental anomalies as well as the challenges in management of this anomaly are discussed. An extensive literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The female to male ratio is 3:1 [3]. In our review, almost 60% of the cases involved women [1,5,7,[10][11][12][13][14][15]. Eleven cases were related to maxillary teeth [3,4,6,8,9,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The female to male ratio is 3:1 [3]. In our review, almost 60% of the cases involved women [1,5,7,[10][11][12][13][14][15]. Eleven cases were related to maxillary teeth [3,4,6,8,9,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 96%
“…Among them, eight were categorized as DO [1,[4][5][6][7][8][9]. Pain or swelling related to a local periapical infection are the main causes of DO discovery, as illustrated in 12 out of the 16 cases [3,4,[6][7][8][9][10][11][12][13][14]. Indeed, one of the most significant clinical concern of DI is the risk of developing pulpal necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, nonsurgical root canal treatment of dens invaginatus, which was characterized by the presence of an open apex, loss of vitality with the presence of periapical cyst formation, was performed and was successful. Meghana and Thejokrishna[ 14 ] suggested that the nonsurgical root canal treatment should be attempted first irrespective of the size of lesion, and surgical intervention must be the second option and is only indicated when non-surgical root canal treatment has failed or the anatomic variations of the canals do not allow access for the biomechanical preparation of the canals. Periapical surgery is indicated in cases of unsuccessful apexification in immature teeth with dens invaginatus and nonvital pulp.…”
Section: Discussionmentioning
confidence: 99%